Internal control/anti-fraud program design for the small business : a guide for companies not subject to the Sarbanes-Oxley Act - Dawson, Steve, 1962- (Hoboken : Wiley, 2015)
"This book covers all elements of an internal control structure applicable to the small business community. It is intended for those businesses for which the Sarbanes-Oxley Act does not apply (non-public businesses). Fraud cases are used throughout the book that provide an analysis of the internal control weaknesses that led to a specific fraud. Each case study also includes relevant controls that could have served to reduce the probability of the occurrence of the fraud. The controls are then summarized according to the five elements of an internal control structure for purpose of assisting in documenting the ultimate anti-fraud program. The steps provided in this book provide readers with a "how to" design and implement an effective and efficient internal control structure/anti-fraud program tailored to their specific needs"--
Rule 2. Place What You Know on the Back Burner, and Think the UnthinkableRule 3. Whether You Like It or Not, You Have to Think Like a Criminal; Rule 4. Don't Overdocument the Process; An Example of Risk Assessment; Procedural Steps for Performing a Fraud Risk Assessment; Understand the Guiding Principles; Determine the Participants; Determine How Information Will Be Gathered; Identify Areas of Fraud Risk; Cash in Bank; Case: The Trail Is Gone; Case: Friends in Low Places; Asset Misappropriation; Corruption; Financial Statement Fraud; PART II: ANTI-FRAUD CONTROL ACTIVITIES: RAISING THE WALLS
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Sarbanes-Oxley Act of 2002 (United States); Fraud -- United States -- Prevention; Small business -- United States -- Auditing; BUSINESS & ECONOMICS / Auditing; Fraud -- Prevention; Small business -- Auditing; Fraud -- United States -- Prevention; Sarbanes-Oxley Act of 2002 (United States).; Small business -- United States -- Auditing; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; United States; Electronic books